Pelvic injury patterns in blast: Morbidity and mortality. Issue 6 (June 2020) - Rankin, Iain A.; Webster, Claire E.; Gibb, Iain; Clasper, Jonathan C.; Masouros, Spyros D.
Abstract : BACKGROUND: Pelvic trauma has emerged as one of the most severe injuries to be sustained by the victim of a blast insult. The incidence and mortality due to blast-related pelvic trauma is not known, and no data exist to assess the relative risk of clinical or radiological indicators of mortality. METHODS: The UK Joint Theater Trauma Registry was interrogated to identify those sustaining blast-mediated pelvic fractures during the conflicts in Iraq and Afghanistan, from 2003 to 2014, with subsequent computed tomography image analysis. Casualties that sustained more severe injuries remote to the pelvis were excluded. RESULTS: One hundred fifty-nine casualties with a 36% overall mortality rate were identified. Pelvic vascular injury, unstable pelvic fracture patterns, traumatic amputation, and perineal injury were higher in the dismounted fatality group ( p < 0.05). All fatalities sustained a pelvic vascular injury. Pelvic vascular injury had the highest relative risk of death for any individual injury and an associated mortality of 56%. Dismounted casualties that sustained unstable pelvic fracture patterns, traumatic amputation, and perineal injury were at three times greater risk (relative risk, 3.00; 95% confidence interval, 1.27–7.09) to have sustained a pelvic vascular injury than those that did not sustain these associated injuries. Opening of the pubic symphysis and at least one sacroiliac joint was significantly associated with pelvic vascular injury ( p < 0.001), and the lateral displacement of the sacroiliac joints was identified as a fair predictor of pelvic vascular injury (area under the receiver operating characteristic curve, 0.73). CONCLUSION: Dismounted blast casualties with pelvic fracture are at significant risk of a noncompressible pelvic vascular injury. Initial management of these patients should focus upon controlling noncompressible pelvic bleeding. Clinical and radiological predictors of vascular injury and mortality suggest that mitigation strategies aiming to attenuate lateral displacement of the pelvis following blast are likely to result in fewer fatalities and a reduced injury burden. LEVEL OF EVIDENCE: Prognostic, level III.